Does the Pricing Capabilities Mediate the Relationship between Total Quality Management Orientation on Radical Innovations? - Ibrahim, Siddig Balal; Mekki, Ossama Hussein; Alfiras, Mohanad; Ateeq, Ali; Danish, Fajer (International Review of Management and Marketing, 2026)
Radical innovation is one of the main indicators that companies always seek to own, however, its link to the approach to total quality through product development capabilities is rarely covered in studies. Therefore, the study sought to know that effect through the use of (RBV) theory and previous studies to evaluate the study model and its hypotheses, by applying it to Sudanese business organizations in Khartoum State. The study also relied on the descriptive and analytical approach, and the questionnaire was used as the main tool for collecting data from the study sample of (300) individuals working in the top management in those companies. And to test the hypotheses of the study; the statistical packages program (SPSS) and (AMOSv25) were used to analyze the data, and the method of path analysis and structural equation modeling was used to test the hypotheses of the study. The study reached a set of results which are: There is a partial relationship between the approach to total quality management and radical innovation. There is a partial relationship between the approach to Total Quality Management and pricing capabilities. There is no relationship between pricing capabilities and radical innovation. There is no mediation of product development capabilities in the relationship between TQM orientation and radical innovation. The result of study extends the body of knowledge in terms of Radical Innovations. Further, it will help policymakers to make relevant decisions related to Radical Innovations.